Effects of water hyacinth biochar on lettuce growth in cadmium-contaminated soil - Zhou, Chunhuo; Wang, Yali; Wei, Li’e; Huang, Huajun; Yu, Chenglong; Yin, Xin (Frontiers in Soil Science, 2022)
Recently, the excessive propagation of water hyacinth led to serious ecological and environmental problems, thereby its treatment and disposal are of great significance. Moreover, remediation of heavy metals in soil is a hot topic at present. Thus, water hyacinth was adopted to prepare biochar to investigate its effect on Cd accumulation in lettuce by pot experiments in this study. The optimal application amount of water hyacinth biochar was 1% (30 t.ha-1) considering the Cd absorption and yield of lettuce plants. Compared with those of control, the application of biochar prepared at 700℃-2h with amount of 3% (90 t.ha-1) resulted in a reduction in Cd by 73.6% and 38.1% in the shoots and roots of lettuce. Within a certain carbonization time (0.5h~2h) and carbonization temperature (300℃~700℃), the content of available Cd in the soil decreases with the increase of the carbonization temperature and time, which might be the main reason for the less Cd concentration in lettuce after applying the biochar. Furthermore, scanning electron microscopy (SEM) and energy dispersive X-ray fluorescence spectroscopy (EDS) analyses showed that Cd was fixed on the biochar in a state of passivation leading to a sharp decrease in the available Cd in the soil. Moreover, it was concluded that the application of biochar brings with it an obvious climb of the enzyme activities increment in the soil up to 2.3 times. Lastly, 16sRNA sequencing has showed that biochar addition leads to the variations of microbial structure and abundance in soil. Accordingly, biochar prepared by water hyacinth can increase lettuce yield and reduce the concentration of heavy metals in lettuce.